HUBUNGAN ANTARA GAYA KOMUNIKASI ASERTIF GURU SEJARAH DAN PARTISIPASI RASIONALITAS KOMUNIKATIF PESERTA DIDIK SMK - Tsafinatun Najah; Agus Suprijono (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT Effective communication plays an important role in creating interactive and participatory history learning. However, students’ ability to engage in rational, critical, and equitable discussions has not yet developed optimally, while studies examining the relationship between teachers’ communication styles and students’ communicative rationality in vocational high school history learning remain limited. This study aimed to analyze the relationship between history teachers’ assertive communication styles and the participation of communicative rationality among eleventh-grade students in public vocational high schools in Sidoarjo Regency. The study employed a quantitative approach with an ex post facto design involving 180 students selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using the Pearson Product-Moment correlation test and simple linear regression with IBM SPSS Statistics. The results revealed a positive and significant relationship between history teachers’ assertive communication styles and students’ participation in communicative rationality, with a moderate level of correlation and a coefficient of determination of 32.1%, while the remaining 67.9% was influenced by factors beyond the scope of this study. The study concludes that history teachers’ assertive communication styles serve as an important foundation for fostering interactive learning; however, their effectiveness requires support from dialogic teaching methods and a psychologically safe classroom environment. ABSTRAK Komunikasi yang efektif berperan penting dalam menciptakan pembelajaran sejarah yang interaktif dan partisipatif. Namun, kemampuan peserta didik untuk terlibat dalam diskusi yang rasional, kritis, dan setara masih belum berkembang secara optimal, sementara penelitian yang mengkaji hubungan gaya komunikasi guru dengan rasionalitas komunikatif peserta didik dalam pembelajaran sejarah di SMK masih terbatas. Penelitian ini bertujuan menganalisis hubungan antara gaya komunikasi asertif guru sejarah dan partisipasi rasionalitas komunikatif peserta didik kelas XI SMK Negeri di Kabupaten Sidoarjo. Penelitian menggunakan pendekatan kuantitatif dengan desain ex post facto yang melibatkan 180 peserta didik melalui purposive sampling. Data dikumpulkan menggunakan angket skala Likert dan dianalisis dengan uji korelasi Product Moment Pearson serta regresi linier sederhana menggunakan IBM SPSS Statistics. Hasil penelitian menunjukkan adanya hubungan positif dan signifikan antara gaya komunikasi asertif guru sejarah dan partisipasi rasionalitas komunikatif peserta didik dengan tingkat hubungan kategori sedang serta kontribusi determinasi sebesar 32,1% sementara 67,9% sisanya dipengaruhi oleh faktor lain di luar penelitian. Penelitian ini menyimpulkan bahwa gaya komunikasi asertif guru sejarah menjadi fondasi penting dalam membangun pembelajaran yang interaktif, namun pengembangannya tetap membutuhkan dukungan metode pembelajaran yang dialogis serta iklim kelas yang aman secara psikologis.